P-Rex1 Cooperates With TGFβR2 to Drive Lung Fibroblast Migration in Pulmonary Fibrosis - Liang, Qing; Chang, Yanhua; Liu, Jing; Yu, Yan; Qiu, Wancheng; Li, Jiajia; Yang, Xu; Sun, Guangchun (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis (PF) is a kind of interstitial lung disease with progressive pulmonary scar formation, leading to irreversible loss of lung functions. TGF-β1/Smad signaling pathway plays a key role in the fibrogenic processes. It is associated with the increased synthesis of extracellular matrix (ECM), enhanced proliferation of fibroblasts, and transformation of alveolar epithelial cells (AECs) into interstitial cells. We investigated P-Rex1, a PIP3-Gβγ-dependent guanine nucleotide exchange factor (GEF) for Rac, for its potential role in TGF-β1 induced pulmonary fibrosis. High expression level of P-Rex1 was identified in the lung tissues from patients with pulmonary fibrosis than that from health donors. Using P-Rex1 knockdown and overexpression system, we established a novel player of P-Rex1 in mouse lung fibroblast migration. P-Rex1 contributed to fibrogenic processes in lung fibroblasts through targeting TGF-β typeⅡreceptor (TGFβR2). RNA-seq analysis for expression profiling confirmed the modulation of P-Rex1 in cell migration and the involvement of P-Rex1 in TGF-β1 signaling. These results identified P-Rex1 as a signaling molecule involved in TGF-β1 induced pulmonary fibrosis, suggesting that P-Rex1 may be a potential target for pulmonary fibrosis treatment.